2019
DOI: 10.1002/jctb.6280
|View full text |Cite
|
Sign up to set email alerts
|

Effective low‐temperature catalytic abatement of benzene over porous Mn‐Ni composite oxides synthesized via the oxalate route

Abstract: BACKGROUND Benzene (C6H6) is a typical kind of volatile organic compound (VOC) which can exert great harm to both human health and the environment, and, thus, which needs to be eliminated before its emission. In this work, porous manganese–nickel (Mn‐Ni) composite oxide catalysts were synthesized through the oxalate route and applied to thermal catalytic oxidation of C6H6. By means of activity tests and relative physico‐chemical characterizations, the factors affecting the activity of those Mn‐Ni composite oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…After investigating the oxidation of o-xylene over Ag/NiO x -MnO 2 prepared by the redox and deposition precipitation methods, Wu et al [7] concluded that good gaseous oxygen activation ability, oxygen bulk mobility, and low-temperature reducibility were the inherent reasons for the high activity of Ag/NiO x -MnO 2 . Guo et al [8] synthesized the porous Mn-Ni composite oxide catalysts via an oxalate route and found that they could effectively catalyze the degradation of benzene at low temperatures, which was related to the good low-temperature reducibility, high oxygen mobility, and large surface areas. Dong et al [9] studied the metal-doped α-MnO 2 catalysts for the combustion of toluene and observed that catalytic oxidation temperature of the Ni-MnO 2 catalyst achieving 90% conversion was 199 • C, and the remarkable low-temperature performance indicated that Ni doping could improve the activity of α-MnO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…After investigating the oxidation of o-xylene over Ag/NiO x -MnO 2 prepared by the redox and deposition precipitation methods, Wu et al [7] concluded that good gaseous oxygen activation ability, oxygen bulk mobility, and low-temperature reducibility were the inherent reasons for the high activity of Ag/NiO x -MnO 2 . Guo et al [8] synthesized the porous Mn-Ni composite oxide catalysts via an oxalate route and found that they could effectively catalyze the degradation of benzene at low temperatures, which was related to the good low-temperature reducibility, high oxygen mobility, and large surface areas. Dong et al [9] studied the metal-doped α-MnO 2 catalysts for the combustion of toluene and observed that catalytic oxidation temperature of the Ni-MnO 2 catalyst achieving 90% conversion was 199 • C, and the remarkable low-temperature performance indicated that Ni doping could improve the activity of α-MnO 2 .…”
Section: Introductionmentioning
confidence: 99%